An interventional pilot study on obesity among low-income patients using a computer-based weight management module - Tracey Doering; Susan Harwell; Cheryl Fassler; Kesley Burr; Sara Hewitt; Christopher Trabue (Greater Baltimore Medical Center, 2013)
Primary care physicians infrequently address lifestyle modification with their obese patients, among whom those of lower economic means are disproportionately represented. To enhance patients’ access to education on lifestyle modification, a clinic-based computer kiosk was installed at our residency clinic for the purpose of healthy lifestyle education. While posttest scores improved and were maintained after completion of lifestyle modification education, body mass index (BMI) was essentially unaffected. Computer-based education without intensive counseling on lifestyle modification appears ineffective in reducing BMI amongst obese patients of lower economic means. Accountable care organization-sponsored health coaching may represent a potential means by which intensive counseling is accomplished among such patients.